ANALISIS KEKUATAN TARIK PADA PENGELASAN SMAW DAN MIG TERHADAP BAJA ST 41 MENGGUNAKAN VARIASI KAMPUH V DAN X - Satria Bayu Handana; Retno Eka Pramitasari (JOURNAL SAINS STUDENT RESEARCH, 2025)
Welding is the process of joining metals by melting the parent metal and filler metal, either with or without the addition of pressure, to produce a strong and continuous joint. This process is critical in various industrial sectors as the quality of the joint directly affects the overall strength, durability and safety of the structure. Therefore, the choice of welding method and the shape of the seam are crucial factors in determining the success of the joint. This study aims to evaluate the effect of variations in the seam shape (V and X) and welding method on the tensile strength of joints in ST 41 steel. The two welding methods used are Shielded Metal Arc Welding (SMAW) and Metal Inert Gas (MIG). Factors such as corner angle, filler metal melting efficiency, heat penetration, and welding arc stability were analyzed to determine their impact on joint strength. Test results show that X-shaped seams tend to produce joints with higher tensile strength than V-shaped seams, due to the angle of the seam which allows for deeper penetration and more even heat distribution. The MIG method also showed superior results to SMAW in terms of joint consistency and quality. However, there was a practical increase in tensile strength in the combination of X-shape and MIG methods, indicating that geometrical factors and welding techniques remain important considerations in welding results.